Strategi Pemasaran Produk Tempe Melalui Digital Marketing - Rahmanda, Via Nabila (Universitas Dehasen Bengkulu, 2023)
Tempe is a food that is very easy for us to find, both raw and tempeh which has been processed into various forms, such as fried foods, chips and so on. Tempe can be said to be one of the foods that is loved by all people, apart from being affordable, tempeh also has quite high vegetable protein, fat, carbohydrates, energy, calcium and minerals. Marketing is an organizational function and a set of processes for creating, communicating and delivering value to customers in order to manage customer relationships in ways that benefit the organization and those interested in the organization. Digital Marketing is a type of marketing that is widely used to promote products or services and to reach consumers using digital channels. Marketing strategy is a plan that outlines industry expectations that there will be an impact of various marketing activities or programs on the demand for a product or these products in a particular target market. Industry uses two or more marketing programs simultaneously.